(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The present study examines the Capital Asset Pricing Model (CAPM) for the Indian stock market from 30 companies of the Nifty Index listed on the National Stock Exchange for the period 1st April 2019 to 31st March 2020 with the help of Black Jensen Scholes Methodology. The findings of this study do not confirm that the basic result of the theory is the time series regression of additional portfolio returns relative to higher levels of returns. The model explains, however, the higher returns and thus supports the linear structure of the CAPM equation. The theory for intercept is that it should be equal to zero and the slope should be equal to the additional return on the market portfolio. The study concludes that Capital Asset Pricing Model holds partially valid in Indian Stock Market.